Intersemiotic And Intrasemiotic Dimensions of Screenplay In Translation - Gayathree, S. (University of Jaffna, 2025)
This study investigates the process of transferring one set of semiotic signs into another across media and genres, with a specific focus on the translation of texts into screenplays and subsequently into audio-visual forms. Drawing on Henrik Gottlieb's concept of intersemiotic adaptational ultrasemiotic translation (IAUT), this research explores how screenplays function as pivotal intermediary texts that both regulate and embody the stages of translation. The primary objectives of this study are to analyze the screenplay's dual function as both a target text (in relation to the written source text) and a source text (for the audio-visual product), to map the semiotic transitions involved in the IAUT process and to examine the dynamic roles of author, screenwriter, and auteur as co-translators in multimedia adaptation. Methodologically, the research employs qualitative textual and semiotic analysis of three selected texts, including two intralingual Tamil translations, to trace the transformation from written linguistic signs to visual-audio signs. These translations are analyzed in terms of both intrasemiotic translation (linguistic to linguistic as text to screenplay) and intersemiotic translation (linguistic to multimedia as screenplay to film). The key findings highlight that IAUT is not a linear process but a layered one, where screenplay mediates two distinct but connected translation acts. The study reveals that screenplay writing constitutes a hybrid translation, blending fidelity, creative intervention, and semiotic negotiation. Furthermore, it emphasizes the need to recognize the screenplay writer's role as a co-author and translator, whose interpretive choices significantly shape the meaning, tone, and cultural resonances of the final filmic product. By situating the discussion within the Tamil cultural and linguistic context, this research contributes to a deeper understanding of intersemiotic translation in regional media practices.
Keywords: Semiology; Intersemiotic Translation; Semiotic sign system; Intermediary text